On a Certain Class of Standard Stress Fields for Plastic Design - Zowczak, W. (Engineering Transactions, 1996)
The paper presents a certain type of statically admissible stress fields that can be useful in plastic design of structural elements of complex shape. lt is shown that these stress fields, constructed with the use of the method of characteristics, give better (more economical) estimates of designed shapes than the fields obtained by means of the piecewise-homogeneous stress field technique. Plastic design of a transversely loaded beam is presented as an example of practical application.